(untitled) (Global Journal of Human-Social Science, 2021)
The present study shares data and information from the experience of Training Environmental Educators (FEA) of the Cultivando Água Boa (CAB) Program of Itaipu Binacional. Based on participatory methodologies, FEA seeks to stimulate reflection and collective action, valuing local knowledge in building more sustainable communities. FEA carries out the federal government’s proposal synthesized in the Environmental Educator Training Program (PROFEA), whose creators are the Ministry of the Environment and the Ministry of Education. This article presents the research results related to the processes of participation in the training of environmental educators and their contribution to the achievement of community environmental governance. The adopted approach was qualitative and as methodological procedures, bibliographic, documentary and field research were used, this was carried out based on observations and interviews.